FITOAKUMULASI MERKURI PADA Cyclosorus interuptus (Willd.) H. Ito., Desmodium gangeticum (L.) DC., DAN Photomorphe subpeltata (Willd.) Mig., DI PENAMBANGAN EMAS TRADISIONAL DUSUN SANGON, KULON PROGO - , NILAM ONERY VIDNIARIZKI; , Dr. Suwarno Hadisusanto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Mercury (Hg) was member of heavy metal group which used in most industrial or mining processes. Distributed globally through atmosphere and then deposited on soil surfaces. Phytoaccumulation involved living plants to absorbs the metal in their growth, big amount metal absorbing ability or living in highly contaminate environment. Currently, there is traditional gold mining activity in Dusun Sangon, Kelurahan Kalirejo, Kecamatan Kokap, Kabupaten Kulon Progo, Provinsi D.I. Yogyakarta. Hence, purpose of this research is to study Cyclosorus interuptus (Willd.) H. Ito., Desmodium gangeticum (L.) DC., dan Photomorphe subpeltata (Willd.) Mig., ability as mercury phytoaccumulator in Dusun Sangonâs traditional gold mining. Sampled plants and soils were taken with 3x3 m2 plot on three locations. Each locations are ranged within 10 (T1), 20 (T2), and 30 m (T3) from tailing collection sink. Next steps are identification, destruction, and mercury concentration quantification with Mercury Lab Analyzer 254. The result shown highest mercury concentration is 17,4 ppm from T1 soil. Average highest value on mercury concentration of Cyclosorus interuptus (Willd.) H. Ito., Desmodium gangeticum (L.) DC., dan Photomorphe subpeltata (Willd.) Mig., are given from T1 location. They are 54,24 Î¼gg-1 from dry root weight and 80,47 Î¼gg-1 from dry crown weight. This research concluded that the soil mercury concentration from particular locations are exceeding normal mercury concentration allowances. Mercury concentration quantity in roots and crowns of Cyclosorus interuptus (Willd.) H. Ito., Desmodium gangeticum (L.) DC., dan Photomorphe subpeltata (Willd.) Mig., are influenced by mercury containing soil.